2018
DOI: 10.1016/j.bbagen.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Selenium unmasks protective iron armor: A possible defense against cutaneous inflammation and cancer

Abstract: This study provides a fresh framework for understanding the seemingly contradictory effects of selenium supplementation. In addition, it offers a novel explanation of how physiologic upregulation of ferroptosis and downregulation of selenoprotein synthesis may mediate resolution of inflammation and carcinogenesis. This is of therapeutic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 75 publications
(68 reference statements)
1
25
0
Order By: Relevance
“…This provides an experimental basis for human islet transplantation and the treatment of type one diabetes 83 . In addition, ferroptosis has been found to play a regulatory role in the progression of the diseases, such as acute myeloid leukemia 84 , age-related macular degeneration (AMD) 85 , psoriasis 86 , and hemolytic disorders 87 . In addition, the relationship between ferroptosis and inflammation is also a hot research topic.…”
Section: Ferroptosis and Other Diseasesmentioning
confidence: 99%
“…This provides an experimental basis for human islet transplantation and the treatment of type one diabetes 83 . In addition, ferroptosis has been found to play a regulatory role in the progression of the diseases, such as acute myeloid leukemia 84 , age-related macular degeneration (AMD) 85 , psoriasis 86 , and hemolytic disorders 87 . In addition, the relationship between ferroptosis and inflammation is also a hot research topic.…”
Section: Ferroptosis and Other Diseasesmentioning
confidence: 99%
“…It is characterized by ROS-induced lipid oxidation and iron overload. Recent findings have suggested that ferroptosis is involved in the pathogenesis of psoriasis, skin cancers, and collagen diseases [ 38 , 39 , 40 ].…”
Section: Roles Of Ros Generated In Skinmentioning
confidence: 99%
“…carbon monoxide and hydrogen sulfide), TGF-ÎČ, formyl-Peptide Receptors, Selenoproteins, Galectin-1, and nucleotides (e.g. adenosine and inosine) , ( Arbiser, Bonner, Ward, Elsey, & Rao, 2018 ; Nelson et al, 2016 ; Wallace, Ianaro, Flannigan, & Cirino, 2015 ). Drugs that stimulate resolution include aspirin, statins, omega-3 fatty acids, annexin A1 and annexin A1-derived peptides, statins, glucocorticoids, diclofenac, α-melanocyte stimulating hormone, erythropoietin, kinase inhibitors, galectins, chemerin, adrenocorticotropic hormone, gaseous mediators (e.g.…”
Section: Therapeutic Approachesmentioning
confidence: 99%